Perancangan Lokapasar Terdistribusi Sebagai Publikasi Kalatog Produk UMKM - Haddad Sammir; Khairil Hamdi (JENTIK, 2025)
The use of information technology in sales is inevitable. There are many approaches that can be used such as developing an online store or joining a popular marketplace. Micro, Small and Medium Enterprises (MSMEs) can use the above methods, but still encounter obstacles such as lack of digital literacy and high resource and cost requirements. Developing a marketplace to support MSMEs also has its own challenges such as high technical requirements and costs. Therefore, this study offers a solution that takes a middle ground by building a distributed marketplace by sharing the technical burden of the marketplace with developers and MSME actors while still prioritizing efficiency and ease of operation.